Learning to teach mathematics in preschool through theory-driven interventions - Björklund, Camilla; Ekdahl, Anna-Lena (NOMAD Nordic Studies in Mathematics Education, 2021)
In this paper we aim to highlight how teachers’ ways of experiencing mathematics teaching for preschoolers is reflected in their teaching acts. The specific research question is how one teacher’s way of experiencing the task of teaching numbers to preschool children change when participating in a professional development project informed by Variation theory principles. We analyze the teaching of one teacher participating in a professional development project during one preschool year with particular interest in how principles for teaching numbers in preschool are implemented in the teacher’s teaching. Observations from authentic teaching situations and an interview with the teacher are data for analysis. From a variation theoretical analysis, we draw conclusions of how the teacher’s ways of experiencing mathematics teaching to preschoolers is reflected in her teaching acts and what challenges there are to implement theory-driven mathematics education in preschool.